A novel translation inhibitor, mersicarpine, inhibits S-phase progression and induces apoptosis in HL60 cells. Issue 1 (7th January 2021) - Shiobara, Tomoko; Nagumo, Yoko; Nakajima, Rie; Fukuyama, Tohru; Yokoshima, Satoshi; Usui, Takeo
Abstract: Mersicarpine is an aspidosperma alkaloid isolated from the Kopsia genus of plants. Its intriguing structural features have attracted much attention in synthetic organic chemistry, but no biological activity has been reported. Here, we report the effects of mersicarpine on human leukemia cell line HL60. At concentrations above 30 µm, mersicarpine reversibly arrested cell cycle progression in S-phase. At higher concentrations, it induced not only production of reactive oxygen species, but also apoptosis. Macromolecular synthesis assay revealed that mersicarpine specifically inhibits protein synthesis. These results suggest that mersicarpine is a novel translation inhibitor that induces apoptosis. Graphical Abstract: